2003
DOI: 10.1051/forest:2003015
|View full text |Cite
|
Sign up to set email alerts
|

A height-diameter model for Pinus radiata D. Don in Galicia (Northwest Spain)

Abstract: -A total of 26 models that estimate the relationship between height and diameter in terms of stand variables (basal area, quadratic mean diameter, maximum diameter, dominant diameter, dominant height, arithmetic mean height, age, number of trees per hectare and site index), were fitted to data corresponding to 9686 trees, using linear and non-linear regression procedures. The precision of the models was then evaluated by cross-validation. The data were collected during two inventories of 182 permanent plots of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 17 publications
3
19
0
3
Order By: Relevance
“…Cox I (López et al 2003) that showed similar values (Tables 3 and 4). The modified model 13 Cox I Mod 1 (López et al 2003) includes the stand variable d g, and the good results obtained with this model are consistent with those obtained for Pinus radiata in Chile (Cox 1994) and in Spain (López et al 2003). However, no references were found for applying these models to Guadua or other bamboo species.…”
Section: Models For Culm Lengthsupporting
confidence: 69%
See 4 more Smart Citations
“…Cox I (López et al 2003) that showed similar values (Tables 3 and 4). The modified model 13 Cox I Mod 1 (López et al 2003) includes the stand variable d g, and the good results obtained with this model are consistent with those obtained for Pinus radiata in Chile (Cox 1994) and in Spain (López et al 2003). However, no references were found for applying these models to Guadua or other bamboo species.…”
Section: Models For Culm Lengthsupporting
confidence: 69%
“…Additionally, other models are also depicted so as to demonstrate the contrast to the best model 13 Cox I Mod. 1 (López et al 2003). In general, the models show a trend towards underestimation in particular for the higher diameter classes; however, model 14 Cox II Mod.…”
Section: Models For Culm Lengthmentioning
confidence: 99%
See 3 more Smart Citations